2019
DOI: 10.1007/s40201-019-00377-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two different carriers in the biodegradation process of an azo dye

Abstract: Purpose The MBBR solution has been applied for the textile wastewater treatment. However, in order to develop cost-effective solutions, waste biomass can be used as carrier. Rice husks are agricultural waste which have been used as an adsorbent of dyes; besides, they can provide and sustain suitable microorganism communities for the degradation of dyes. This study aimed to evaluate the biodegradation of the azo dye Direct Red 75 in two treatment systems with different carriers. Methods Bioreactor A was compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…However, few studies have investigated the potential of rice husks as a significant carbon source for bacterial growth and as an accelerator in the dye degradation process. In a previous study, the azo dye Direct Red 75 was decolorized by 90% using a biofilter-sequenced anaerobic–aerobic system, with rice husks employed as carriers as a source of microorganisms [ 45 ]. In the current study, we introduced a strongly active extremophilic bacterial strain that has multiple functions—illustrating its high efficiency in dye degradation and using rice husks as a valuable carbon source for the bacteria’s growth and metabolism during the degradation process ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have investigated the potential of rice husks as a significant carbon source for bacterial growth and as an accelerator in the dye degradation process. In a previous study, the azo dye Direct Red 75 was decolorized by 90% using a biofilter-sequenced anaerobic–aerobic system, with rice husks employed as carriers as a source of microorganisms [ 45 ]. In the current study, we introduced a strongly active extremophilic bacterial strain that has multiple functions—illustrating its high efficiency in dye degradation and using rice husks as a valuable carbon source for the bacteria’s growth and metabolism during the degradation process ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Pearce et al [57], the optimum temperature for color removal is between 35 and 45 ºC. Santos-Pereira et al [65] reported an increase in the color removal of Direct Red 75 (DR75), in an anaerobic MBBR, from 45% at 21 ± 2 °C to 85% at 30 ± 0.5 °C (Table 1).…”
Section: • Temperaturementioning
confidence: 96%
“…According to Table 1, anaerobic conditions were used in most of the studies, in which biological color removal was achieved [15,23,27,39,48,55,65,68,81]. Castro et al [14] and Park et al [55] evaluated the performance of aerobic MBBRs in dye degradation and reported that no significant color removal was observed in the presence of oxygen.…”
Section: Cellmentioning
confidence: 99%
See 2 more Smart Citations